The using of random models under composites diagnostics by low velocity impact method - Єременко, В. С.; Марченко, Б. Г.; Мокійчук, В. М. (Proceedings of National Aviation University (archive), 2021)
There is described possibilities of Hilbert random processes using for mathematics modeling of information signals under diagnostics of composite materials. The experimental result which confirm variation of random characteristics of process depend upon defects in product is carried out.